Efektivitas Program Kuliah Kerja Mahasiswa UNTIRTA Sebagai Bentuk Tridharma Perguruan Tinggi Dalam Memajukan Kesejahteraan Masyarakat - Putra, Arif Mardatul; Jazuli, E Rakhmat (Universitas Sultan Ageng Tirtayasa, 2024)
ABSTRACTImplementation of the Student Work Lecture program, the implementation of which is that students only use Student Work Lecture activities as formal activities to fulfill academic requirements. The goals that are expected to solve community problems and advance community welfare are not properly considered and actualized. As for identifying the problem, what is the effectiveness of the Student Work Study program as a form of the Tridharma of Higher Education as stated in Law Number 12 of 2012 concerning Higher Education in advancing community welfare? and What are the obstacles to the effectiveness of the Sultan Ageng Tirtayasa University Student Work Lecture program as a form of the Tridharma of Higher Education in advancing community welfare based on Law Number 12 of 2012 concerning Higher Education? The theories in this research are, Legal Effectiveness Theory and Welfare Theory. The research method is empirical juridical. The research specification is descriptive analysis. The data source is primary data supported by secondary data. The data collection technique is interviews. Data was obtained and analyzed descriptively using a qualitative approach method. The results of the research are based on the indicators mentioned by Soerjono Soekanto, namely, Legal Factors, Regulations governing Tridharma are clearly regulated in the Law, Law Enforcement Factors, supervision of implementation has not been carried out properly, Means or Facilities Factors, the process of fulfilling the facilities for students who are looking for , determining and even financing it yourself, Community Factors, the implementation of work programs created by students is still far from achieving community prosperity, Cultural Factors, the cultural culture of students who still do not have legal awareness. The obstacles faced are; Constraints on student performance, lack of supervision of the implementation of Student Work Lectures, Failure to Provide Facilities. The conclusion is that, based on the 5 (five) indicators, only 1 (one) is effective, namely Legal Factors, then 4 (four) are ineffective, namely Law Enforcement Factors, Community Factors , Facilities and Facilities Factors, Cultural Factors. It can be concluded based on this that Student Work Lectures have not been effective for the past 3 (three) years. Suggestions: It is necessary to carry out good supervision and make efforts to increase students' self-awareness regarding the implementation of the Student Work Lecture program, and facilities and facilities must be provided.Keywords: Tridharma of Higher Education, Student Work Study, Public Welfare. ABSTRAKPelaksanaan program Kuliah Kerja Mahasiswa, pelaksanaannya mahasiswa hanya menjadikan kegiatan Kuliah Kerja Mahasiswa sebagai kegiatan formalitas pemenuhan syarat akademis. Tujuan yang diharapkan menyelesaikan permasalahan masyarakat dan memajukan kesejahteraan masyarakat tidak diperhatikan dan diaktualisasikan dengan baik. Adapun identifikasi masalahnya, Bagaimana efektivitas program Kuliah Kerja Mahasiswa sebagai bentuk dari Tridharma Perguruan Tinggi yang tertuang dalam Undang- Undang Nomor 12 Tahun 2012 Tentang Pendidikan Tinggi dalam memajukan kesejahteraan masyarakat? dan Bagaimana kendala efektivitas program Kuliah Kerja Mahasiswa Universitas Sultan Ageng Tirtayasa sebagai bentuk Tridharma Perguruan Tinggi dalam memajukan kesejahteraan masyarakat berdasarkan Undang-Undang Nomor 12 Tahun 2012 tentang Pendidikan Tinggi?. Teori dalam penelitian ini yaitu, Teori Efektivitas Hukum dan Teori Kesejahteraan. Metode penelitian yaitu, yuridis empiris. Spesifikasi penelitian yaitu deskriptif analisis. Sumber data yaitu data primer yang ditunjang oleh data sekunder. Teknik pengumpulan data adalah wawancara. Data diperoleh dan dianalisis secara deskriptif dengan metode pendekatan kualitatif. Hasil penelitian berdasarkan Indikator yang telah disebutkan oleh Soerjono Soekanto yaitu, Faktor Hukum, Peraturan yang mengatur Tridharma sudah diatur secara jelas didalam Undang-Undang, Faktor Penegak Hukum, pengawasan pelaksanaan belum dilakukan dengan baik, Faktor Sarana atau Fasilitas, proses pemenuhan fasilitas Mahasiswa yang mencari, menentukan bahkan mebiayai sendiri, Faktor Masyarakat, pelaksanaan program kerja yang dibuat oleh mahasiswa masih jauh dalam mencapai kesejahterakan masyarakat, Faktor Kebudayaan, kultur budaya mahasiswa yang masih belum memiliki kesadaran hukum. kendala yang dihadapi yaitu; Kendala kinerja mahasiswa, kurangnya pengawasan pelaksanaan Kuliah Kerja Mahasiswa, Tidak Diberikannya Fasilitas Kesimpulannya yaitu, berdasarkan dari 5 (lima) indikator hanya 1 (satu) yang efektif yaitu Faktor Hukum, kemudian 4 (empat) tidak efektif, yaitu Faktor Penegak Hukum, Faktor Masyarakat, Faktor Sarana dan Fasilitas, Faktor Kebudayaan. disimpulkan berdasarkan hal tersebut bahwa Kuliah Kerja Mahasiswa belum efektif selama periode waktu 3 (tiga) tahun belakang, Saran, Perlunya melakukan pengawasan dengan baik dan melakukan upaya meningkatkan kesadaran diri mahasiswa mengenai pelaksanaan program Kuliah Kerja Mahasiswa, serta harus dipenuhinya sarana dan fasilitas. Kata Kunci: Tridharma Perguruan Tinggi, Kuliah Kerja Mahasiswa, Kesejahteraan Masyarakat.